Augustine on the Katechon: A Lesson from De Civitate Dei. - DOMÍNGUEZ, PATRICIO; ELLIS, ERIK (Scripta Mediaevalia, 2023)
This article presents Augustine’s exegesis of the controversial eschatological passage of 2 Thessalonians 7 through analysis of Roman virtue in the context of the role of the Roman Empire in divine providence. In contrast to many of the Greek and Latin fathers, Augustine’s evaluation of Rome’s providential role is primarily negative: he says the Roman empire and the virtus upon which it rests are sinful but that the evils of Roman power restrain (hence katechon) worse evils. This interpretation, most clearly expressed in his City of God, differentiates Augustine from his contemporaries’ view of Rome and makes him a sui generis thinker in this regard.